COVID-19: ANALYSIS OF CONFIRMED CASES IN TERESINA, PIAUI, BRAZIL - Araújo, Agostinho Antônio Cruz (2020)
Introduction: Coronavirus are microorganisms responsible for causing respiratory infections that can vary from asymptomatic to severe. The spread of the virus around the world has led to a pandemic position, which has claimed numerous victims. Given the magnitude of the problem, the study aims to analyze the epidemiological profile of confirmed cases of COVID-19 in Teresina-PI. Design: Descriptive and epidemiological study. The study population consisted of 315 confirmed cases of Covid-19, in individuals residing in the city of Teresina-PI, between March and April 2020. The variables evaluated were: age group, sex, deaths confirmed by Covid- 19 and confirmed cases of Covid-19 by area of ​​the city. Results: There was a predominance of confirmed cases of Covid-19 in young, female individuals living in an urban area of ​​Teresina. Most deaths occurred in the elderly, being more prevalent in males. Implications: The epidemiological monitoring of cases strengthens the need to implement preventive measures, such as social containment. In addition, the expansion of testing in the population is important in order to identify asymptomatic cases and, consequently, to prevent the spread of the coronavirus, considering that these cases favor the transmission chain.